Discrimination between different E-box-binding proteins at an endogenous target gene of c-myc. - Laurie Desbarats; Stefan Gaubatz; Martin Eilers (1996)
c-myc plans a key role in regulating mammalian cell proliferation and apoptosis. The gene codes for a transcription factor, Myc, that belongs to the helix-loop-helix/leucine zipper (HLH/LZ) family of proteins. Myc heterodimerizes with a partner protein termed Max; the heterodimeric complex binds to CAC(G/A)TG (E-box) sequences and activates transcription from these sites. However, several other HLH/LZ proteins, including USF and TFE-3, bind to and trans-activate from the same element, yet have no documented effect on cell proliferation or apoptosis. Therefore, it is likely that mechanisms exist that discriminate between these proteins for activation of natural target genes of Myc. We now show that trans-activation from the E-box in the rat prothymosin-alpha intron enhancer is indeed specific for Myc, and identify both the distance from the start site of transcription and a second E-box element adjacent to that recognized by Myc as critical determinants of specificity. Surprisingly, transcription activation domains required for Myc to activate from this distal enhancer position differ from previously mapped domains and closely correlate with those domains essential for transformation. As observed in transformation assays, Myc and Max strongly synergize in activation from a distal enhancer position. Our data suggest that trans-activation from the prothymosin intron enhancer is a faithful reflection of the transforming properties of the Myc protein.